Competition and Incentives with Motivated Agents - Besley, Timothy; Ghatak, Maitreesh (American Economic Review, 2005)
A unifying theme in the literature on organizations such as public bureaucracies and private nonprofits is the importance of mission, as opposed to profit, as an organizational goal. Such mission-oriented organizations are frequently staffed by motivated agents who subscribe to the mission. This paper studies incentives in such contexts and emphasizes the role of matching the mission preferences of principals and agents in increasing organizational efficiency. Matching economizes on the need for high-powered incentives. It can also, however, entrench bureaucratic conservatism and resistance to innovations. The framework developed in this paper is applied to school competition, incentives in the public sector and in private nonprofits, and the interdependence of incentives and productivity between the private for-profit sector and the mission-oriented sector through occupational choice.